An experimental method for studying Young's modulus of single crystal silicon at high temperature. (December 2013) - Yao, Shaokang; Xu, Dehui; Xiong, Bin; Wang, Yuelin
This article reports a novel indirect experimental method to measure Young's modulus of single crystal silicon at high temperature. Young's modulus at high temperature is estimated by measuring the elastic deformation of single crystal silicon microstructure at room temperature and high temperature. Since it is difficult to measure the elastic deformation directly at high temperature, a novel indirect method is presented in this study. In order to prevent plastic deformation at high temperature, the Von Mises yield criterion is applied to predict the onset of plastic deformation. The resulting Young's modulus of single crystal silicon is about 110 ± 17 GPa at 900 °C in the <100> direction from the present experiment.